2008
DOI: 10.1177/0266242608088743
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptualization of the Determinants of Small Business Website Adoption

Abstract: As evidence mounts on the importance of small businesses and the opportunities presented by website adoption globally, it becomes important to understand the key issues that determine website adoption. However, the extant literature relating to small business website adoption is fragmented and fails to provide an understanding of what determines adoption.Therefore the key contribution of this article to current knowledge is the development of a conceptualization, supported by the literature, that will provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 114 publications
(227 reference statements)
2
134
1
5
Order By: Relevance
“…En el ámbito específico de e-Commerce, también se han identificado aspectos relevantes que afectan su adopción, como la actitud de la dirección de empresa frente al e-Commerce (Simmons et al, 2008) y conocimientos y actitudes del personal que inciden en su implementación (Bruque y Moyano, 2007); en Latinoamérica, los estudios efectuados siguen sentido similar, por ejemplo, Nasco et al (2008) estiman que las actitudes de jefaturas de empresas chilenas inciden en su intención de adoptar eCommerce en las organizaciones que dirigen. Las investigaciones mencionadas reconocen que conocimientos y actitudes de directivos de empresas afectan la adopción de tecnología y e-Commerce en sus organizaciones, en coherencia con esta evidencia, se estima que la participación de microemprendedores en programas de formación, se relaciona en forma positiva con uso de Internet y desarrollo de actividades eCommerce en sus empresas.…”
Section: Marco Teóricounclassified
“…En el ámbito específico de e-Commerce, también se han identificado aspectos relevantes que afectan su adopción, como la actitud de la dirección de empresa frente al e-Commerce (Simmons et al, 2008) y conocimientos y actitudes del personal que inciden en su implementación (Bruque y Moyano, 2007); en Latinoamérica, los estudios efectuados siguen sentido similar, por ejemplo, Nasco et al (2008) estiman que las actitudes de jefaturas de empresas chilenas inciden en su intención de adoptar eCommerce en las organizaciones que dirigen. Las investigaciones mencionadas reconocen que conocimientos y actitudes de directivos de empresas afectan la adopción de tecnología y e-Commerce en sus organizaciones, en coherencia con esta evidencia, se estima que la participación de microemprendedores en programas de formación, se relaciona en forma positiva con uso de Internet y desarrollo de actividades eCommerce en sus empresas.…”
Section: Marco Teóricounclassified
“…As mentioned earlier, SME play an invaluable role in countries' competitiveness and the world economy. Furthermore, they have unique features that distinguish them from large businesses (Simmons et al, 2008): they have a small market share; they are often managed by owners in a personalised way; they generally lack human and capital resources. Hence, website evaluation criteria should take these features into account.…”
Section: Website Evaluation Of Smementioning
confidence: 99%
“…This is rather surprising, as small and medium-sized enterprises (SME) account for ~90% of enterprises and more than 50% of employment worldwide (World Bank, 2013), along with the fact that SME have unique features (Simmons et al, 2008). Furthermore, the rare exceptions analyse only a limited set of content features and sometimes a few design features, or are confined to certain sectors (Burgess et al, 2011;Kim et al, 2011;Meroño-Cerdan and Soto-Acosta, 2007;Puentes et al, 2012;Schmidt et al, 2008;Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on SMEs adoption on the web emphasized the inherent characteristics and abilities of the owner/ manager as being key determinants of web adoption (Simmons et al, 2008;Bengtsson et al, 2007;Bharati and Chaudhury, 2006;Martin and Matlay, 2003;Barba-Sanchez et al, 2007). Based on an empirical study, Bharati and Chaudhury (2006) found that top management and customers were the main determinants for technology adoption by high-tech U.S. manufacturing firms.…”
Section: Internet Adoption By Smesmentioning
confidence: 99%